Intravesical monitoring of intra‐abdominal pressure after renal transplantation in children: A safety and feasibility study. (13th August 2020) - Wagner, Jula; Herden, Uta; Fischer, Lutz; Schild, Raphael; Vettorazzi, Eik; Herrmann, Jochen; Ebenebe, Chinedu Ulrich; Singer, Dominique; Deindl, Philipp
Abstract: IAH after RTX can threaten graft viability. This study aimed to assess the feasibility and safety of longitudinal IAP measurements as an IAH screening method in children after RTX. A cohort of eight children with a mean ± SD [range] age 9.6 ± 6.2 [2‐17] years who underwent RTX and 18 control patients were evaluated between May 2017 and February 2018. We compared longitudinal IAP measurements using a Foley manometer to other clinical monitoring data. In total, 29 IAP measurements were performed in RTX patients and 121 in controls. The mean post‐operative IAP was 7.4 ± 4.3 [1‐16] mm Hg following RTX and 8.1 ± 3.7 [1‐19] mm Hg in controls. We noted IAH in 9 (31%) of 29 IAP measurements after RTX and in 41 (34%) of 121 IAP measurements in controls. No graft dysfunction occurred in RTX patients despite elevated IAP values. The mean ± SD [range] time expenditure for IAP measurement was 2.1 ± 0.4 [0.6‐3.2] minutes. No severe complications occurred during the IAP measurements. Analysis of longitudinal IAP measurements demonstrated that IAP measurement is safe and feasible in children recovering from renal transplantation in the PICU.